2021
DOI: 10.1007/s00127-021-02027-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between types of UK national newspapers, illness classification, and stigmatising coverage of mental disorders

Abstract: Background Media coverage on mental health problems has been found to vary by newspaper type, and stigma disproportionately affects people with mental illness by diagnosis. Objective This study investigated the relationships between types of UK national newspaper (tabloid vs. broadsheet), illness classification (SMI–severe mental illnesses vs. CMD–common mental disorders), and stigmatising coverage of mental disorders, and whether these relationships chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
4
13
0
Order By: Relevance
“…The breaches from these news sources were not found to be a direct result of syndication on these platforms, with approximately one quarter of these breaches being from syndicated sources. These findings are consistent with recent research from the United Kingdom, which shows that reporting on people with mental illness in tabloid-style newspapers tends to be more stigmatizing than in other news sources (Li et al, 2021). Proactive and targeted approaches to working with these media outlets may help to improve their understanding of the Mindframe media guidelines and their quality of reporting on mental illness, and subsequently drive down the number of StigmaWatch reports received related to these media outlets.…”
Section: Discussionsupporting
confidence: 92%
“…The breaches from these news sources were not found to be a direct result of syndication on these platforms, with approximately one quarter of these breaches being from syndicated sources. These findings are consistent with recent research from the United Kingdom, which shows that reporting on people with mental illness in tabloid-style newspapers tends to be more stigmatizing than in other news sources (Li et al, 2021). Proactive and targeted approaches to working with these media outlets may help to improve their understanding of the Mindframe media guidelines and their quality of reporting on mental illness, and subsequently drive down the number of StigmaWatch reports received related to these media outlets.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, while the role of media in disseminating information about mental illness is important (Ross et al, 2019), it can also be biased, sensationalized. Mistaken newspaper coverage on mental illnesses, or myths perpetuated about mental illnesses can adversely impact the public's perception of people living with severe mental disorders (SMI) (Li et al, 2021). This negative media coverage can contribute to a harmful social environment that facilitates the rejection, discrimination, stigmatization, and marginalization of people living with a SMI (Dinos et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of articles relating to mental health from UK newspapers between 2008 and 2019 demonstrated that tabloid newspapers were 32% more likely to be stigmatising compared to broadsheet newspapers (Li et al, 2021). In particular, they found that tabloid newspapers were more likely to stigmatise those with serious mental illness.…”
Section: Introductionmentioning
confidence: 99%